Understanding adolescent low back pain from a multidimensional perspective: Implications for management - O'Sullivan, Peter; Smith, Anne; Beales, Darren; Straker, Leon (2017)
Copyright © 2017 Journal of Orthopaedic & Sports Physical Therapy®. SYNOPSIS: Low back pain (LBP) is the leading cause of disability worldwide. It often begins in adolescence, setting a course for later in life. We have tracked the course of LBP in the Raine Study cohort from the age of 14 years into early adulthood. Our work has found that LBP is already prevalent in individuals at 14 years of age and increases throughout adolescence and into early adulthood. It is often comorbid with other musculoskeletal pain. For some adolescents, LBP has little impact; for others, its impact includes care seeking, taking medication, taking time off from school and work, as well as modifying physical and functional activity. Of concern is the increasing prevalence of LBP with impact across adolescence, reaching adult rates by 22 years of age. The predictors of disabling LBP in adolescence are multidimensional. They include female sex, negative back pain beliefs, poor mental health status, somatic complaints, involvement in sports, and altered stress responses. Genetics also plays a role. Ironically, the factors that we have historically thought to be important predictors of LBP, such as "poor" spinal posture, scoliosis, carrying school bags, joint hypermobility, and poor back muscle endurance, are not strong predictors. This challenges our clinical beliefs and highlights that adolescent LBP needs a flexible and targeted multidimensional approach to assessment and management. In most cases, we recommend a cognitive functional approach that challenges negative LBP beliefs, educates adolescents regarding factors associated with their LBP, restores functional capacity where it is impaired, and encourages healthy lifestyle habits.